Pengaruh Budaya Organisasi Dan Kompetensi Terhadap Motivasi Pegawai Dinas Kepemudaan Dan Olahraga Provinsi NTT - Marselinda A. Hege (Jurnal Administrasi Terapan, 2024)
The performance and productivity of a public organization greatly depends on the motivation of its employees. In the context of the East Nusa Tenggara (NTT) Provincial Youth and Sports Service, employee motivation is a crucial factor in achieving strategic goals related to developing the potential of youth and sports. Therefore, understanding the factors that influence employee motivation in this service is very important. The aim of this research is to determine the influence of organizational culture and competency on employee motivation at the NTT Province Youth and Sports Service. The research approach used is exploratory survey analysis. Research was conducted at the NTT Provincial Youth and Sports Service. The location was chosen by researchers considering, among other things, that the framework that was developed and the variables that emerged could be carried out throughout Indonesia with different backgrounds but still for Civil Servant respondents. The number of samples used was 99 people. The types of data collected are primary data and secondary data. Data analysis uses multiple regression analysis. The results obtained: organizational culture and employee competence influence the work motivation of employees of the NTT Provincial Youth and Sports Service at a confidence level of 99%. This means that the higher the organizational culture (values ​​that employees follow) and employee competence, the higher the employee motivation and vice versa, if the organizational culture and competence are lower, the lower the employee motivation. The role of organizational culture shapes the character of human resources in implementing and achieving organizational goals, so it is very important for organizations to increase employee motivation in order to build cooperation to achieve common goals.